A self-sustaining process model of inertial layer dynamics in high Reynolds number turbulent wall flows. (13th March 2017) - Chini, G. P.; Montemuro, B.; White, C. M.; Klewicki, J.
Abstract : Field observations and laboratory experiments suggest that at high Reynolds numbers Re the outer region of turbulent boundary layers self-organizes into quasi-uniform momentum zones (UMZs) separated by internal shear layers termed 'vortical fissures' (VFs). Motivated by this emergent structure, a conceptual model is proposed with dynamical components that collectively have the potential to generate a self-sustaining interaction between a single VF and adjacent UMZs. A large- Re asymptotic analysis of the governing incompressible Navier–Stokes equation is performed to derive reduced equation sets for the streamwise-averaged and streamwise-fluctuating flow within the VF and UMZs. The simplified equations reveal the dominant physics within—and isolate possible coupling mechanisms among—these different regions of the flow. This article is part of the themed issue 'Toward the development of high-fidelity models of wall turbulence at large Reynolds number'.